Voices heard. Autobiographical accounts of language learning after forced migration. (3rd September 2022) - Thüne, Eva-Maria; Brizić, Katharina
Abstract: Learning a new language after forced migration has hardly ever been studied from the perspective of children. Their viewpoint, however, gets even more important, if we want to understand the lifelong consequences of their early experiences. With this aim, we use autobiographical accounts of persons who were rescued from Nazi Germany and brought to Great Britain in 1938 by an operation known as Kindertransport. The Kindertransportees' memories of learning English are precious also with regard to the 21st century, where the share of minors in forced migration is steadily increasing, and where language teachers are struggling with the task of successfully teaching the newly arrived students. Our contribution aims to inform teacher education by building on the sociolinguistic concept of Voice, and exemplifying what a favourable context for language learning might look like in times of increasing forced migration.